Evaluation of Differential Protection in a Main Power Transformer: A Case Study in PT Pertamina Geothermal Energy Area of Kamojang - Altama, Gady; Mustar, Muhamad Yusvin; Syahputra, Ramadoni; Prasetyo, Teguh Iman (Journal of Electrical Technology UMY, 2019)
The electric power system consists of various components, ranging from the components of generation, transmission, and distribution. The systems are quite expensive, so that excellent, reliable, and economic protection is needed to avoid internal and external faults.Â  The faults can trigger damage to components, especially on the main transformers in the Power Plant Geothermal Unit 4 of the Kamojang area managed by PT Pertamina Geothermal Energy. Disturbances that occur in the main transformers of various types so that the primary protection needed in the transformer is a differential relay to protect to avoid interference that occurs. This study discusses the comparison of theoretical differential relay calculation calculations with actual differential relay setting data in the Kamojang Unit 4 Geothermal Power Plant and simulates with ETAP 12.6 software. The problem that occurs in the main transformer of the Geothermal Power Unit Unit 4 Kamojang area is the difference in the slope 1 of the actual setting data with a mathematical calculation that is the actual setting data of 40% and the numerical calculation data worth 8.5%. Please note that the minimum slope one limit is 5%. PT Pertamina Geothermal Energy made slope one changes, so that differential relays are not too sensitive to the interference current that occurs within the protection zone of differential relays.